0461 Does "TIB" Differentiate Between Good Sleepers and Subjects That Develop Acute or Chronic Insomnia? A 2nd Analyses. (25th May 2022) - Perlis, Michael; Morales, Knashawn; Grandner, Michael; Posner, Donn; Vargas, Ivan; Seewald, Mark; Muench, Alexandria; Boyle, Julia; Ellis, Jason
Abstract: Introduction: According to the 3P model of insomnia, the variable that mediates the transition from acute to chronic insomnia is "sleep extension" (the behavioral tendency to expand sleep opportunity to compensate for sleep loss). Recently, this proposition was prospectively evaluated by assessing how Time-in-Bed (TIB) varied, week-by-week, relative to the incidence of acute insomnia in four groups, those that: maintained good sleep (GS, n=911), recovered good sleep (AI-REC, n=244); had persistent poor sleep (AI-PPS, n=65); and developed chronic insomnia (AI-CI, n=23)). Significant differences for pre-to-post acute insomnia TIB were not detected for the insomnia groups (as compared to one another or as compared to GSs). The observed trends suggested that the increases in TIB observed were minor (< 15 min overall, at 2 weeks, and at 12 weeks post AI). In the present analysis, a more granular evaluation was undertaken to assess whether sleep extension occurs on the nights following poor sleep bouts. Methods: The same data set and subject groups were modeled for TIB occurring on the night following a poor night's sleep (≥ 30 min for SL or WASO or EMA) for the post-acute insomnia interval (by weekday and weekend). Linear mixed effects model was used to account for up to 1 year of repeated nights per subject. Results: During the weekdays, the groups did not differ with respect to TIB following a poor nights' sleep. On average, the four groups (including good sleepers) did not vary TIB by more than 5 minutes. During the weekends, all four groups tended to restrict TIB. In this instance, AI-CI subjects restricted TIB the least (AI-CI -17.2[5.11]; (GS -25.7[SE 1.58]; AI-PPS -27.6[6.1]; AI-REC -32.3[1.9]. Conclusion: As with the prior analysis, the transition to CI does not appear to be triggered by sleep extension. In the present analysis there is some evidence to support the notion that AI-CI subjects restrict TIB less. This counterintuitive finding needs to be further evaluated taking into account sleep timing. That is, time-to-bed and time-out-of-bed may vary (show the attempt to extend sleep opportunity) while TIB does not change appreciably (owing to limitations in sleep ability [plasticity]). Support (If Any): Support: R01AG041783;K24AG055602;R01AT003332